Diversity and Local Uses of Tree Species of Non-Timber Forest Products in Zamay Forest Reserve in Cameroon - Konsala, Souare; Moksia, Froumsia; Yougouda, Hamawa; Evele Moctar, Sassouang; Tchobsala, .; Adamou, Ibrahima (International Journal of Environment, 2020)
Forest products play an important role in supporting livelihoods in many developing countries. The study examined diversity and local uses of non-timber forest products (NTFPs) in Zamay forest reserve in Cameroon. The inventory design consisted of three collection units (CU): CU1,  CU2 and CU3 in the north, center and south of the reserve respectively. In each CU, seven plots of 2 500 m2 each (50 m × 50 m) were established and woody individuals (dbh ≥ 10 cm) were inventoried. Local uses of NTFP were determined through semi-structured and structured interviews and plot methods were used for the inventory of the resource species. Statistical analyses were performed with Origin 6.0 and XLSTAT Softwares. A total of 745 stems was recorded, representing fifty-two species grouped in twenty-two families and thirty-seven genera. The Shannon diversity index (H’) varied from 2.52 to 3.11, and Shannon evenness index (EQ) from 0.75 to 0.83. The most dominant families were Combretaceae, Burseraceae, Balanitaceae and Mimosaceae. A total of 44 useful species was recorded in five categories of uses: medicine, food, fodder, crafts and fertilizers. The most important species in terms of use values were Acacia albida Del., Anogeissus leiocarpus (DC.) Guill. & Perr., Khaya senegalensis (Desr.) A. Juss., Balanites aegyptiaca L., Ziziphus mauritiana Lam., Tamarindus indica L. and Sclerocarya birrea (A. Rich.) Hochst. Means of frequency of citation and use values were not significantly different. Results of this survey will allow considering reforestation with valued species in the degraded parts of the reserve.